Assessment of Long-Term Surface Water Quality in Mekong River Estuaries Using A Comprehensive Water Pollution Index: 10.32526/ennrj/21/20230158 - Tran, Thai Thanh; Liem, Nguyen Duy; Hieu, Ha Hoang; Tam, Huynh Thanh; Mong, Nguyen Van; Yen, Nguyen Thi My; Yen, Tran Thi Hoang; Quang, Ngo Xuan; Luu, Pham Thanh (Environment and Natural Resources Journal, 2023)
Surface water quality (SWQ) has been degraded in the Mekong River Basin under increasing pressures of population growth, economic development, and global climate change. This study employed the comprehensive water pollution index (CWPI) to assess the spatio-temporal variation of SWQ in the downstream Mekong River estuaries. Eight water quality parameters were measured between 2005 and 2021 at 21 sampling sites downstream of the Mekong River. These parameters included total suspended solids (TSS), biological oxygen demand (BOD5), chemical oxygen demand (COD), ammonia (N-NH4+), nitrate (N-NO3-), phosphate (P-PO43-), iron (Fe), and total coliform. Most of the monitoring locations in the estuaries of Ham Luong, Cua Dai, Ba Lai, and Co Chien exhibited slightly to moderately polluted conditions, as indicated by the CWPI values ranging from 0.67-2.91, 0.41-2.20, 0.27-3.02, and 0.37-2.95, respectively. TSS and Fe concentrations consistently exceeded the allowable limits, while the majority of values for N-NH4+, N-NO3-, P-PO43-, and coliform remained within acceptable thresholds. Additionally, parameters indicative of organic pollution, namely BOD5 and COD, displayed a noticeable upward trend between 2005 and 2021. SWQ exhibited significant spatial and temporal variations with TSS, organic matter, nutrients, and iron being the main areas of concern. These findings can provide guidance to policymakers involved in the assessment and enhancement of water quality in the presence of pollutant compounds that lead to a decline in water quality.